Differentiation between Focal Malignant Marrow-Replacing Lesions and Benign Red Marrow Deposition of the Spine with T2(*)-Corrected Fat-Signal Fraction Map Using a Three-Echo Volume Interpolated Breath-Hold Gradient Echo Dixon Sequence - Kim, Yong Pyo (Korean J Radiol, 2014)
OBJECTIVE: To assess the feasibility of T2(*)-corrected fat-signal fraction (FF) map by using the three-echo volume interpolated breath-hold gradient echo (VIBE) Dixon sequence to differentiate between malignant marrow-replacing lesions and benign red marrow deposition of vertebrae. MATERIALS AND METHODS: We assessed 32 lesions from 32 patients who underwent magnetic resonance imaging after being referred for assessment of a known or possible vertebral marrow abnormality. The lesions were divided into 21 malignant marrow-replacing lesions and 11 benign red marrow depositions. Three sequences for the parameter measurements were obtained by using a 1.5-T MR imaging scanner as follows: three-echo VIBE Dixon sequence for FF; conventional T1-weighted imaging for the lesion-disc ratio (LDR); pre- and post-gadolinium enhanced fat-suppressed T1-weighted images for the contrast-enhancement ratio (CER). A region of interest was drawn for each lesion for parameter measurements. The areas under the curve (AUC) of the parameters and their sensitivities and specificities at the most ideal cutoff values from receiver operating characteristic curve analysis were obtained. AUC, sensitivity, and specificity were respectively compared between FF and CER. RESULTS: The AUCs of FF, LDR, and CER were 0.96, 0.80, and 0.72, respectively. In the comparison of diagnostic performance between the FF and CER, the FF showed a significantly larger AUC as compared to the CER (p = 0.030), although the difference of sensitivity (p = 0.157) and specificity (p = 0.157) were not significant. CONCLUSION: Fat-signal fraction measurement using T2(*)-corrected three-echo VIBE Dixon sequence is feasible and has a more accurate diagnostic performance, than the CER, in distinguishing benign red marrow deposition from malignant bone marrow-replacing lesions.